Preferência manual e assimetrias intermanuais de desempenho na ação de alcançar em bebês - Souza, Rosana Machado de (Universidade Federal de São Carlos, 2010)
Manual preference has been regarded as derived from innate performance advantage of one hand over the other. The main purpose of this work was to investigate the relationship between manual preference and intermanual performance asymmetry on a task of reaching for static targets in five-month-old infants. Secondary purposes were to assess the effects of spatial target position and gender on manual preference, and the relationship between the infants‟ and the parents‟ manual preference. Manual preference was evaluated through frequency of right- and left-handed reaching toward targets at right, midline and left positions, regarding the midsagittal plane of the infant‟s body. Intermanual asymmetry was assessed through kinematic analysis of reaching toward the target at the midline position. Dependent variables were the following: movement time, movement straightness, number of movement units, median velocity, peak velocity, and deceleration time. Analysis of manual preference indicated similar frequency of rightand left-handed reaching at midline and ipsilateral reaching toward lateral targets. Analysis of manual preference regarding toy positions indicated the equivalence between the incidence of infants presenting right and left manual preference. Kinematic analysis showed similar patterns of reaching between the right and left hands, except for deceleration time. Manual preference was not correlated with performance asymmetry. These results suggest that early manual preference in reaching does not derive from a superior capacity of control of one hand over the other. Manual preference was not significantly different between males and females, and it was not correlated with parents‟ manual preference. Results are discussed in terms of environmental versus genetic factors associated with formation of manual preference.
Manual preference and intermanual performance asymmetries in infants reaching
Keywords: Fisioterapia; Desenvolvimento motor; Controle motor; Alcance manual; Lactentes; Assimetrias intermanuais de desempenho; Alcance; Bebê; Laterality; Manual preference; Handedness; Intermanual performance asymmetries; Reaching; Infant; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL